OVERVIEW OF THE SIGNS AND SIMPTOMS OF PRE MENSTRUAL SYNDROME IN YOUNG WOMEN IN SMK N 9 SURAKARTA - Pawestri, Deni Riya; Untari, Ida (JURNAL PROFESI || MEDIA PUBLIKASI PENELITIAN, 2014)
Pre Menstrual Syndrome (PMS) is collection of physical symptoms, psychological, and emotion associated with the menstrual cycle. Approximately 80 to 90 percent of women at child-bearing age experience pre menstrual symptoms that can interfere aspects of her life. The symptoms are usually predictable and occur regularly on a two-week period before menstruation. Based on a preliminary survey conducted by the researchers by interviewing five SMKN 9 Surakarta students, the results showed that the most important symptoms of pre-menstrual was breast pain. In addition, they also experienced abdominal pain, body fatigue, dizziness, and decreased concentration. The purpose of this study is to know overview of the signs and symptoms of pre-menstrual syndrome in young women in SMKN 9 Surakarta. This research used descriptive survey research method. The sample was taken by random sampling technique for 132 people. The instrument was Â a questionnaire with univariat analysis. The results showed that the signs and symptoms of pre menstrual syndrome experienced by in young women in the form physical symptoms the most were changes in appetite 72,7 % (96 people), form of psychological symptoms experienced the most were irritabilitas (easily offended) 87,1 % (115 people), form of behavioral symptoms the most experienced were loss of concentration 39,4 % (52 people), as well as additional symptoms not listed in questionnaire appeared the most were abdominal pain 20,5 % (27 people). The conclusions in this study is overview of the signs and symptoms of pre-menstrual syndrome in young women in SMKN 9 Surakarta is the young women experienced physical symptoms (38,50%) , psychological symptoms (58,30%), behavioral symptoms (27,4%), additional symptoms not listed in questionnaire appears (4,2%). Â  Keywords: Signs and Symptoms, Pre Menstrual Syndrome, Young Women